Investigação de abordagens híbridas para sistemas de recomendação implícitos - Silva, Jonathan Gouvea da (Universidade Federal de São Carlos, 2020)
This project deals with the investigation of implicit recommender systems, in relation to the accuracy and versatility of the systems, and of the hybridization as a tool to improve these performance metrics. Databases of users's musical habits where used.
Investigation on hybrid approaches to implicit recommender systems
Keywords: Sistemas de recomendação; Dados implícitos; Recomendações de músicas; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO